2020
DOI: 10.1017/s1473550420000208
|View full text |Cite
|
Sign up to set email alerts
|

Contact inequality: first contact will likely be with an older civilization

Abstract: First contact with another civilization, or simply another intelligence of some kind, will likely be quite different depending on whether that intelligence is more or less advanced than ourselves. If we assume that the lifetime distribution of intelligences follows an approximately exponential distribution, one might naively assume that the pile-up of short-lived entities dominates any detection or contact scenario. However, it is argued here that the probability of contact is proportional to the age of said i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
(45 reference statements)
2
16
0
Order By: Relevance
“…Spada & Melini (2020) extended the work of DeVito (2019) arguing that our lack of contact with alien species is best explained if the growth rate of communicative species is logarithmic, or at best sub-linear. Kipping et al (2020) rigorously justified our expectation that when contact is made it will be with a species that has been technological for far longer than humans, and why this expectation is robust even if most technological species do not last very long. Döbler (2020) discussed the assumptions he claims underlie "orthodox" radio SETI, in particular the problematic nature of assuming a common path of technological development among many species, and explores the importance of "technological synchronicity."…”
Section: The Drake Equation and The Fermi Paradoxmentioning
confidence: 71%
“…Spada & Melini (2020) extended the work of DeVito (2019) arguing that our lack of contact with alien species is best explained if the growth rate of communicative species is logarithmic, or at best sub-linear. Kipping et al (2020) rigorously justified our expectation that when contact is made it will be with a species that has been technological for far longer than humans, and why this expectation is robust even if most technological species do not last very long. Döbler (2020) discussed the assumptions he claims underlie "orthodox" radio SETI, in particular the problematic nature of assuming a common path of technological development among many species, and explores the importance of "technological synchronicity."…”
Section: The Drake Equation and The Fermi Paradoxmentioning
confidence: 71%
“…In this regard, the expected age of civilizations whose technosignatures we might detect is of issue. Recently, Kipping et al (2020) have shown that, in a galaxy hosting an exponential distribution of civilization ages, long-lived civilizations will be favoured in detection efforts (Fig. 6).…”
Section: Planetary Intelligence and Long-lived Civilizationsmentioning
confidence: 99%
“…When, on average, civilizations find evidence of others of comparable age, the relation falls along the diagonal line. Using Bayesian methods,Kipping et al (2020) demonstrated that the actual detection curve will likely follow a convex curve implying that detected civilizations will be older than the civilizations carrying out the search. Thus, for reasons of longterm sustainability, these older detected civilizations may have already passed through the transition in planetary intelligence to a mature technosphere discussed in the text.…”
mentioning
confidence: 99%
“…After another hundred (or million) years of advancement, it will perhaps appear obvious to any civilization that every reasonable other civilization will have converged on the best solution (which is quantum) in almost no time. After all, it is likely that most civilizations are older and more advanced than ourselves (Kipping et al 2020). .…”
Section: Quantum Supremacymentioning
confidence: 99%